ANALISIS DETERMINAN AUDIT REPORT LAG - Gilang Satrya Ramadhan; Majidah Majidah; Eddi Budiono (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2018)
The purpose of this research is to determine the effect of leverage, size of company, audit quality and accounting result simultaneously or partially to the audit report lag. The type of this research is descriptive verificative. The number of manufacturing companies in the Indonesia Stock Exchange (BEI) over the period of 2011-2015 are 143 companies, then obtained a sample of 110 by purposive sampling. Analysis of data is carried out using multiple regression method. The results showed variable leverage, size company, audit quality and accounting result can explain audit report lag 33.3%. Partial test results showed that leverage did not significantly affect, size company and accounting result have a significant negative effect and audit quality have a significant positive effect on audit report lag.